Annotated bibliography on medical and veterinary entomology in the Philippines - Ricaforte, Ella T.; Buenviaje, Rufo Q. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1978)
This annotated bibliography is a compilation of research studies and literature on medical and veterinary entomology common to the Philippines from 1930-1975. It is arranged by arthropod groups and alphabetically by author under each group. Each entry is numbered consecutively from 001-504. No indexing by scientific name is made unless contained in the title or whenever the title is vague.
Each entry includes the following information: author and title of article, title of periodical, title or book from where it was taken, volume number, date of publication and pagination. The compilation includes informative annotations of research studies undertaken during the period. Where the entries are semi-popular in nature, descriptive annotations are provided.
Author and keyword indexes derived from titles are included at the end of the bibliography to facilitate the location of specific items. References are to item numbers and not page numbers.
Mimeographed.
Special Problem (Master of Library Science)
Keywords: Insects as carriers of disease -- Bibliography; Veterinary entomology -- Bibliography